The Relationship between Service Quality and Patient Satisfaction in Telemedicine Services - Fadli Fadli; Khairunnisa Khairunnisa; Emmaculata Advensy Rara; Denaya Nindita; Kosasih (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Service quality is a critical factor influencing patient satisfaction in the use of telemedicine services. This study aims to analyze service quality, patient satisfaction level, and the relationship between service quality and patient satisfaction with telemedicine services. A quantitative research method with a cross-sectional design was employed. The sample consisted of 74 respondents selected using probability sampling with a cluster sampling technique. Data were collected using a questionnaire based on the SERVQUAL dimensions utilizing a 1–4 Likert scale. Data analysis was performed using the Pearson product-moment correlation test after meeting the normality and linearity assumptions. The results show that the quality of telemedicine services is in the very good category, with a percentage of 95.9%, while the level of patient satisfaction is also very high at 98.6%. Pearson correlation results indicate a positive and significant relationship between service quality and patient satisfaction (r = 0.773, p < 0,001). All SERVQUAL dimensions have a significant relationship with patient satisfaction, showing the strongest correlation among the dimensions. In conclusion, the study demonstrates that the higher the quality of telemedicine services, the higher the level of patient satisfaction. Therefore, telemedicine providers are encouraged to continuously improve service quality to maintain optimal patient satisfaction.